The Grameen Bank approach - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
In 1976, Dr Muhammed Yunus, Professor of Economics at Chittagong University, Bangladesh, began a programme to help bring the rural poor into a viable banking network. This was transformed in 1983 into the independent Grameen (village) Bank; a bank...